Spatiotemporal chaotic one-way Hash function construction based on coupled tent maps - LIU Jian-dong; FU Xiu-li (Tongxin xuebao)
A novel coupled tent maps-based spatiotemporal chaotic cryptographic Hash function was proposed.Compared with the discrete tent map,the coupled discrete tent spatiotemporal chaotic maps have longer computer-realization-period,nearly uniform distribution and desired diffusion and confusion properties.Based on the coupled discrete tent spatiotemporal chaotic maps,a cryptographic Hashing function is constructed to generate 128-bit Hash value from a message with arbitrary length.The approach uses the initial value of coupled discrete tent chaotic dynamical system iteration as the secret key.The key space is very large.There is a high sensitivity and complex and strongly nonlinear coupling relation between the Hash value and the corresponding message and secret key.Theoretic analysis and simulation results are shown that the approach possess not only extremely high security in comparison with earlier chaotic Hash functions,but also the high execution speed.Therefore,the approach can satisfy all the performance requirements of Hash function,such as one-way,key sensitivity and collision resistance.